2007
DOI: 10.1088/0031-9155/52/20/n03
|View full text |Cite
|
Sign up to set email alerts
|

Megavoltage x-ray skin dose variation with an angle using grid carbon fibre couch tops

Abstract: It is well known that a skin dose from high-energy x-ray radiation varies with the angle of beam incidence or the presence of a radiotherapy linear accelerator couch top material. This note investigates changes produced to the skin dose from a Varian carbon fibre grid couch top at differing angles of incidence for 6 MV x-rays as is often the case clinically. Results have shown that the skin dose can easily be measured using an EBT Gafchromic film whereby the delivered skin dose can be quantified to a high leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 19 publications
0
31
0
Order By: Relevance
“…It is important to assess this loss in skin sparing because lack thereof could result in side effects such as induced erythema, moist desquamation and permanent hair loss [8]. The loss of skin sparing from megavoltage photons when using CF has been documented in the literature for different couch designs [32-35]. The early work by Meara and Langmack [8] noted an increase in build up with respect to Dmax of 47-56% through different carbon fiber combinations compared to 17.8% with no CF for 6 MV photon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to assess this loss in skin sparing because lack thereof could result in side effects such as induced erythema, moist desquamation and permanent hair loss [8]. The loss of skin sparing from megavoltage photons when using CF has been documented in the literature for different couch designs [32-35]. The early work by Meara and Langmack [8] noted an increase in build up with respect to Dmax of 47-56% through different carbon fiber combinations compared to 17.8% with no CF for 6 MV photon.…”
Section: Discussionmentioning
confidence: 99%
“…The early work by Meara and Langmack [8] noted an increase in build up with respect to Dmax of 47-56% through different carbon fiber combinations compared to 17.8% with no CF for 6 MV photon. Butson et al [35] reported that for the Varian Exact TM tabletop, the maximum skin dose (defined at a depth of 0.15 mm), for a 10 cm × 10 cm 6MV photon field was 55% compared to 19% for open field.…”
Section: Discussionmentioning
confidence: 99%
“…Our corresponding measured attenuations were 1.9% and 2.7%. Butson et al ( 8 ) used GAFCHROMIC EBT films to measure the increase in skin dose with a Varian carbon fiber grid couchtop. With a direct posterior 6 MV beam and a field size of 10×10cm2, the skin dose increased from 27% with no buildup to 55%.…”
Section: Discussionmentioning
confidence: 99%
“…The magnitude of skin dose will increase with the angle of incidence of the beam. ( 8 ) That is, the presented values are the best‐case scenarios with respect to skin doses when treating through the couchtop. The reader should also keep in mind that, in this study, we only investigated the couch inserts and not any immobilization devices or possible couch rails which also contribute to the beam attenuation.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically EBT Gafchromic has been utilized for high energy and low energy radiotherapy / diagnostic dosimetry [7][8][9][10][11][12][13][14] . Some of its characteristics which have defined its usefulness include high spatial resolution 15 and near energy independence 16 .…”
Section: Introductionmentioning
confidence: 99%